Designing with Web standards - Zeldman, Jeffrey (Voices that matter., 2007)
Best-selling author, designer, and web standards evangelist Jeffrey Zeldman has updated his classic, industry-shaking guidebook. This new edition--now in full color--covers improvements in best practices and advances in the world of browsers since the first edition introduced the world to standards-based design. Written in the same engaging and witty style, making even the most complex information easy to digest, it remains an essential guide to creating sites that load faster, reach more users, and cost less to design and maintain. Readers will learn from Jeffrey's insights as he demonstrates how web standards are driving search engine friendliness ("findability") and the Web 2.0 applications that have reinvigorated the medium and the online marketplace. Readers will discover new techniques to make CSS layouts work better across multiple browsers and ways to make web content more accessible. Designing with Web Standards is an AIGA Design Press book, published under Peachpit's New Riders imprint in partnership with AIGA.